Differences in expression of the cancer stem cell marker aldehyde dehydrogenase 1 among estrogen receptor-positive/human epidermal growth factor receptor type 2-negative breast cancer cases with early, late, and no recurrence. Issue 1 (December 2016) - Miyoshi, Yuichiro; Shien, Tadahiko; Ogiya, Akiko; Ishida, Naoko; Yamazaki, Kieko; Horii, Rie; Horimoto, Yoshiya; Masuda, Norikazu; Yasojima, Hiroyuki; Inao, Touko; Osako, Tomofumi; Takahashi, Masato; et al.
Abstract Background The significance of the expression of aldehyde dehydrogenase 1 (ALDH1), a cancer stem cell marker, for predicting the recurrence of estrogen receptor (ER)-positive/human epidermal growth factor receptor type 2 (HER2)-negative breast cancer is still poorly understood. The value of ALDH1 in predicting the time of recurrence remains unknown. Methods In total, 184 patients with early distant recurrence, 134 patients with late distant recurrence, and 321 control patients without recurrence for more than 10 years after starting initial treatment for ER-positive/HER2-negative breast cancer, registered in 9 institutions, were analyzed. We assessed relationships between ALDH1 and other clinicopathological features, and ALDH1 expression was compared among the three groups. The relationship between ALDH1 expression and overall survival after recurrence was also evaluated in each group. Results The rates of ALDH1 expression positivity (more than 1 %) in the early, late, and no recurrence groups were 18.4 %, 13.4 %, and 8.4 %, respectively. ALDH1 expression correlated significantly with lymph node metastases (p  = 0.048) and the Ki-67 labeling index (p  < 0.001) in the early recurrence group. Multivariate analysis revealed ALDH1 expression to be significantly higher in the early recurrence group than in the no recurrence group (adjusted OR 2.140, 95 % CI 1.144–4.003, p  = 0.016). Moreover, there was a significant difference in ALDH1 expression between the early and no recurrence groups receiving adjuvant endocrine therapy and chemotherapy (adjusted OR 4.625, 95 % CI 1.881–12.474, p  < 0.001). However, there was no difference in ALDH1 expression between the late and no recurrence groups in univariate analysis (OR 1.507, 95 % CI 0.738–2.998, p  = 0.253). In multivariate analysis, ALDH1 was not a factor independently predicting overall survival after the detection of recurrence (adjusted OR 1.451, 95 % CI 0.985–2.085, p  = 0.059). Conclusions Among patients with ER-positive/HER2-negative breast cancer, ALDH1 expression was more common in those with early recurrence, and this expression was found to be associated with a more aggressive breast cancer phenotype than that in the patients without recurrence. Further study is needed to clarify the prognostic significance of the heterogeneity of cancer stem cells and to confirm their role in resistance to chemotherapy.